1997
DOI: 10.1507/endocrj.44.89
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Hyperprolactinemia in Patients with Hashimoto's Thyroiditis.

Abstract: Abstract.The causes of hyperprolactinemia, the correlation between serum levels of PRL and thyroid function and magnetic resonance imaging (MRI) of the pituitary were studied in patients with chronic thyroiditis.Seventy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 7 publications
5
24
0
1
Order By: Relevance
“…Elevation of PRL in overt hypothyroidism has been reported before [1-4, 8, 12], but studies on this subject in patients with subclinical hypothyroidism are few [9,10,11]. Several mechanisms have been proposed for the increase in prolactin levels in primary hypothyroidism.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Elevation of PRL in overt hypothyroidism has been reported before [1-4, 8, 12], but studies on this subject in patients with subclinical hypothyroidism are few [9,10,11]. Several mechanisms have been proposed for the increase in prolactin levels in primary hypothyroidism.…”
Section: Discussionmentioning
confidence: 93%
“…PRL levels remained high in those who received placebo. Notsu, et al [10] measured PRL levels in 15 healthy controls and in 74 Hashimoto's thyroiditis patients: 42 were euthyroid, 18 had sublcinical and 14 had overt hypothyroidism. PRL was found to be elevated in 42% of the overt hypothyroid patients, 11% in the subclinical hypothyroid patients, and 14% or the euthyroid patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seminal abnormalities were corrected when patients became euthyroid. Another study that evaluated the effects of Grave's disease on male reproduction showed that thyrotoxic male presented several changes on semen parameters, such as: asthenospermia, hypospermia, oligospermia, necrospermia and teratospermia, as well as complaints of impaired sexual function (49). A normalization of 85% of seminal alterations was observed when euthyroidism were reached.…”
Section: Thyroid Hormone Disorders and Male Reproductionmentioning
confidence: 99%
“…An increase in the production rate of estrogens is also observed in some men with thyrotoxicosis, although it is unclear whether this is due to increased production of adrenal androgen precursors (specifically D4A) or to other mechanisms (48). Furthermore, serum progesterone was reported to be higher in hyperthyroid than in euthyroid males (49), while mean basal testosterone bioactivity was lower in patients as compared to controls (50). Thyrotoxic males often present clinical features compatible with exposure to increased estrogen bioactivity (gynecomastia, spider angiomas, and a decrease in libido) (51).…”
Section: Thyroid Hormone and Testicular Functionmentioning
confidence: 99%